Inclusive participatory approaches: A facilitator’s guide - Zaremba, Haley; Elias, Marlène; Devi, J. Tulasi; Priyadarshini, Pratiti (2021)
In community engagement and participatory processes, facilitators must make intentional efforts and adopt inclusive strategies to include marginalized and frequently overlooked groups. Yet, there is a lack of guidance on how to inclusively facilitate participatory processes. Facilitators are therefore often poorly prepared to engage with the power relations that underlie these processes, including those between the facilitator and participants and among participants themselves. This guide addresses this shortcoming by presenting strategies that have been shown to enhance the meaningful participation of women and marginalized groups in participatory processes. The aim is to equip facilitators with tools to create inclusive participatory spaces and community engagement. Although it refers to processes related to natural resource management, the guide is also applicable to the facilitation of participatory processes focusing on other issues or fields of significance to communities.